Heinrich Isaac and Polyphony for the Proper of the Mass in the Late Middle Ages and Renaissance. Red. David J. Burn, Stefan Gasch. Turnhout 2011 - Grzegorz Kos (Muzyka)
Rezencja książki Heinrich Isaac and Polyphony for the Proper of the Mass in the Late Middle Ages and Renaissance red. David J. Burn, Stefan Gasch